Changes in Muscles and Tendons Due to Neural Motor Disorders: Implications for Therapeutic Intervention - A. L. Hof (Neural Plasticity)
Patients with an upper motor neurone syndrome (CP) suffer from many disabling primary symptoms: spasms, weakness, and loss of dexterity. These primary ‘neurogenic’ symptoms often lead to secondary disabilities, muscle contractures, and tertiary effects, bone deformations. A common symptom of CP is hypertonia, with. the consequence that the involved muscles remain in an excessively shortened length for most of the time. As a normal reaction of the muscle tissue, the number of sarcomeres is reduced and the muscle fibers shorten permanently: a contracture develops. A possible second type of contracture is that normal muscle lengthening along with bone growth is affected. Current treatments for the secondary effects include (1) reduction of muscle force, (2)lengthening of the muscle fibers by serial plaster casts, and (3)surgical lengthening of tendons or aponeurosis. The choice of treatment depends on the cause of the functional deficit. Bone tissue also adapts itself to abnormal forces, especially in the growth period. The hypertonias or contractures of CP so may give rise to bone malformations that interfere with function (e.g. femur endorotation) or may reduce the action of muscles by changing the lever arm (e.g. ankle varus). Although prevention should always be preferred, a timely surgical intervention cannot always be avoided. The differences in treatment for the various groups require and justify an extensive laboratory investigation, including EMG recordings in gait, measurement of passive elastic properties, and long-term observation of the hypertonia.